2021
DOI: 10.1016/j.cattod.2020.10.042
|View full text |Cite
|
Sign up to set email alerts
|

Hydrodeoxygenation of m-cresol as a depolymerized lignin probe molecule: Synergistic effect of NiCo supported alloys

Abstract: Three bimetallic Ni-Co (Ni:Co ratio 1:3, 1:1 and 3:1) and two monometallic (Ni and Co) nanoparticles supported on Al2O3 were synthesized by incipient wet impregnation and characterized by various technics (N2-physisorption, XRD, H2-TPR, CO-chemisorption and elemental analysis). It was demonstrated by XRD that NiCo alloys nanoparticles were present on bimetallic solids. The catalytic properties of all catalysts were determined for the hydrodeoxygenation of m-cresol at 340 °C under 4 MPa of total pressure. It wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(8 citation statements)
references
References 68 publications
1
7
0
Order By: Relevance
“…The ICP‐OES analysis further confirms the presence of 21.9 wt.% and 26.1 wt.% of Ni and Co, respectively, approximate equal to a Ni/Co molar ratio of 1, again confirming the formation of bimetallic nanoalloys. Furthermore, H 2 ‐TPR results (Figure S5) show shift of reduction temperature of NiCo catalyst (496°C) compared to that of Ni/C (480°C) and Co/C (533°C), indicating the formation of NiCo nanoalloy 47 …”
Section: Resultsmentioning
confidence: 97%
“…The ICP‐OES analysis further confirms the presence of 21.9 wt.% and 26.1 wt.% of Ni and Co, respectively, approximate equal to a Ni/Co molar ratio of 1, again confirming the formation of bimetallic nanoalloys. Furthermore, H 2 ‐TPR results (Figure S5) show shift of reduction temperature of NiCo catalyst (496°C) compared to that of Ni/C (480°C) and Co/C (533°C), indicating the formation of NiCo nanoalloy 47 …”
Section: Resultsmentioning
confidence: 97%
“… the direct deoxygenation (DDO route) leading to toluene, either by the direct cleavage of the C−O bond or by involving the formation of a tautomer intermediate (3‐methyl‐3,5‐cyclohexadienol) with further hydrogenation of its carbonyl group; the hydrogenation (HYD route) in which the aromatic ring is first hydrogenated yielding 3‐methylcyclohexanone and 3‐methylcyclohexanol with further dehydration to produce methylcyclohexenes and final hydrogenation to methylcyclohexane. Direct cleavage of 3‐methylcyclohexanol to methylcyclohexane can also be considered [6d,16] . The hydrogenation route also involves the passage through the tautomer intermediate (3‐methyl‐3,5‐cyclohexadienol) which can be considered as a common intermediate of both DDO and HYD routes. …”
Section: Resultsmentioning
confidence: 99%
“…Numerous studies on Ni-Co mixed oxide reduction by the H2-TPR method have been reported. For example, Goncalves et al [30] The catalysts prepared at 80 Pa exhibited a very similar course of reduction as those prepared at 15 Pa, with a slight shift to higher temperatures with an increasing amount of cobalt in the catalysts. The reduction of the binary Ni-Co oxide catalysts showed an indication of peak splitting into two parts, which may involve either the reduction of several different components present in the catalysts or the reduction of particles of different sizes.…”
Section: Temperature-programmed Reductionmentioning
confidence: 91%